In fetuses with congenital lung masses, decreased ventricular and atrioventricular valve dimensions are associated with lesion size and clinical outcome. (1st December 2019) - Mardy, Christopher; Blumenfeld, Yair J.; Arunamata, Alisa A.; Girsen, Anna I.; Sylvester, Karl G.; Halabi, Safwan; Rubesova, Erika; Hintz, Susan R.; Tacy, Theresa A.; Maskatia, Shiraz A.
Abstract: Introduction: The clinical importance of mass effect from congenital lung masses on the fetal heart is unknown. We aimed to report cardiac measurements in fetuses with congenital lung masses and to correlate lung mass severity/size with cardiac dimensions and clinical outcomes. Methods: Cases were identified from our institutional database between 2009 and 2016. We recorded atrioventricular valve (AVVz) annulus dimensions and ventricular widths (VWz) converted into z scores, ratio of aortic to total cardiac output (AoCO), lesion side, and congenital pulmonary airway malformation volume ratio (CVR). Respiratory intervention (RI) was defined as intubation, extracorporeal membrane oxygenation (ECMO), or use of surgical intervention prior to discharge. Results: Fifty‐two fetuses comprised the study cohort. Mean AVVz and VWz were below expected for gestational age. CVR correlated with ipsilateral AVVz ( R S = −.59, P < .001) and ipsilateral VWz (−0.59, P < .001). Lower AVVz and AoCO and higher CVR were associated with RI. No patient had significant structural heart disease identified postnatally. Conclusion: In fetuses with left‐sided lung masses, ipsilateral cardiac structures tend to be smaller, but in our cohort, there were no patients with structural heart disease. However, smaller left‐sided structures may contribute to the need for RI that affects a portion of these fetuses. Abstract : What's already known about this topic? Larger congenital lung masses are associated with worse neonatal outcomes Congenital lung masses can cause mass effect on the fetal heart, but the physiologic implications and clinical relevance of this are unknown. In congenital diaphragmatic hernia, another space‐occupying lesion in the chest, there is an increased risk of left heart hypoplasia and left‐sided obstructive defects, eg, aortic coarctation. What does this study add? This is the first study to examine the relationship between congenital lung masses and fetal cardiac dimensions. On average, cardiac dimensions in fetuses with lung masses are smaller for gestational age. Left‐sided congenital lung mass size correlates with smaller mitral valve and left ventricular dimensions. Despite relative left heart hypoplasia in fetuses with left‐sided lung masses, no patient in this cohort developed left‐sided obstructive cardiac disease.